2015
DOI: 10.1038/srep10027
|View full text |Cite
|
Sign up to set email alerts
|

Breast cancer cell line MCF7 escapes from G1/S arrest induced by proteasome inhibition through a GSK-3β dependent mechanism

Abstract: Targeting the ubiquitin proteasome pathway has emerged as a rational approach in the treatment of human cancers. Autophagy has been described as a cytoprotective mechanism to increase tumor cell survival under stress conditions. Here, we have focused on the role of proteasome inhibition in cell cycle progression and the role of autophagy in the proliferation recovery. The study was performed in the breast cancer cell line MCF7 compared to the normal mammary cell line MCF10A. We found that the proteasome inhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 39 publications
2
15
0
1
Order By: Relevance
“…Because studies have proposed induction of autophagy as a resistance mechanism to proteasome inhibitor treatment in breast cancer cells 31 32 , we performed immunoblotting analysis to determine how MLN9708 treatment affects the autophagy machinery. Cells were treated with MLN9708 (0.1 μM) for 24 h and then were incubated with drug-free medium for 24 h, 48 h, or 72 h. The results show that MLN9708 induced autophagy marker LC3A/B-I/II expression in the cell lines tested ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Because studies have proposed induction of autophagy as a resistance mechanism to proteasome inhibitor treatment in breast cancer cells 31 32 , we performed immunoblotting analysis to determine how MLN9708 treatment affects the autophagy machinery. Cells were treated with MLN9708 (0.1 μM) for 24 h and then were incubated with drug-free medium for 24 h, 48 h, or 72 h. The results show that MLN9708 induced autophagy marker LC3A/B-I/II expression in the cell lines tested ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Recent report had been reported that it can regulate the proliferation of human ovarian cancer cells in vitro (SKOV3 and ES‐2 cells) as well as in vivo . Study also showed that the relevance of GSK‐3 β as a target for controlling cell cycle progression and proliferative capacity in MCF7, highlighted the cotreatment of breast cancer . However, the deep molecular mechanism of the regulation by GSK‐3 β on CRC and its signaling pathway worths further investigation.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the proportion of G0/G1 phase cells returned to control levels in response to 50 nM MG132 or 50 nM Bortezomib. Although we did not examine the expression level of cyclins or CDK, proteasome inhibitors may result in the changes of protein level of cyclins and CDK to inhibit degradation by proteasome as shown in previous reports (34 , 35) .…”
Section: Discussionmentioning
confidence: 97%